2010
DOI: 10.1371/journal.pone.0013877
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Pattern of Retinal Nerve Fiber Layer in Multiple Sclerosis. High Resolution Optical Coherence Tomography: Potential and Limitations

Abstract: BackgroundRecently the reduction of the retinal nerve fibre layer (RNFL) was suggested to be associated with diffuse axonal damage in the whole CNS of multiple sclerosis (MS) patients. However, several points are still under discussion. (1) Is high resolution optical coherence tomography (OCT) required to detect the partly very subtle RNFL changes seen in MS patients? (2) Can a reduction of RNFL be detected in all MS patients, even in early disease courses and in all MS subtypes? (3) Does an optic neuritis (ON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 18 publications
3
52
0
3
Order By: Relevance
“…Up till now, a reliable specific para-clinical marker neither for the diagnosis nor for monitoring disease activity of MS could yet be established (e.g. Aboul-Enein et al, 2010;Gilmore et al, 2010;Kuhle et al, 2007;Serbecic et al, 2010Serbecic et al, , 2011.…”
Section: Diagnostic Criteria and The Disease Course Of Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Up till now, a reliable specific para-clinical marker neither for the diagnosis nor for monitoring disease activity of MS could yet be established (e.g. Aboul-Enein et al, 2010;Gilmore et al, 2010;Kuhle et al, 2007;Serbecic et al, 2010Serbecic et al, , 2011.…”
Section: Diagnostic Criteria and The Disease Course Of Msmentioning
confidence: 99%
“…Fourteen MRS studies were published with no significant NAA changes in the NAWM in a total of 184 CIS or 263 RRMS patients (Davie et al, 1997;Sarchielli et al, 1998;Brex et al, 1999;Kapeller et al, 2002;Fernando et al, 2004;Ruiz-Pena et al, 2004;Vrenken et al, 2005;Mathiesen et al, 2005;Srinivasan et al, 2005;Khan et al, 2005;Khan et al, 2008;Kirov et al, 2008;Bellmann-Strobl et al, 2009;Aboul-Enein et al, 2010).…”
Section: No Significant Changes Of Naa Ratios or Naa Concentrationsmentioning
confidence: 99%
“…Some studies have shown the presence of subclinical optic neuropathy in MS patients, which can be diagnosed by performing not only OCT, but such multiple tests as visual evoked potentials, visual field examination, visual acuity, and colour vision. [25][26][27] According to the literature, in the early stages of ON in MS patients, RNFL and macular thinning or thickening (swelling) can occur, along with different structural changes in optic disc morphology. 27,28 The retina in MS patients passes through stages of minimal demyelination, remyelination, and gliosis, which can be verified only by biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] According to the literature, in the early stages of ON in MS patients, RNFL and macular thinning or thickening (swelling) can occur, along with different structural changes in optic disc morphology. 27,28 The retina in MS patients passes through stages of minimal demyelination, remyelination, and gliosis, which can be verified only by biopsy. 29 Some researchers consider that OCT is relatively insensitive for revealing acute axon damage at the time of acute presentation and even later, and that non-neural tissue components in RNFL may obscure subtle degrees of axonal loss in MS. 11,30 We think that some of our patients without pronounced visual symptoms or complaints could have had subclinical changes in the optic nerve during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation